Biculturalism Leading to Third Space Identity: A Postcolonial Analysis of Elif Shafak’s The Island of Missing Trees (Al-Qamar, 2023)
The current paper aims to highlight biculturalism in immigrants which leads to Third Space Identity in host countries. The study will explore the construction of third space identity in the protagonist Ada Kazantzakis by analyzing the theme of hybridization in Elif Shafak’s novel,’ The Island of Missing Trees’ (2021). Homi K. Bhabha’s theory of third space and hybridity is the key to maneuver the existing research. Bhabha’s leading role in postcolonial theory provokes the study towards the world famous book The Location of Culture (2021) by scoring the conceptual imperatives and political consistency of postcolonial Cyprus during 1974 in the novel, ‘The Island of Missing Trees’ (2021). Qualitative method is used for data collection. The objective of the study is to find out how biculturalism in immigrants leads to third space identity and how it affects the protagonists’ life in the novel. This research will be beneficial in bringing of modern themes and the way Shafak’s dealt with these themes artistically.
Keywords: Biculturalism; Postcolonialism; Ada Kazantzakis; Shafak’s Cyprus; Third Space Identity